Associação entre coesão de grupo e estados de humor pré-competitivo de atletas juvenis - Foschiera, Diogo Bertella (2021)
The Profile of Mood States is a psycho-social variable associated to sports performance, which can be also characterized as multidimensional and ephemeral, and it can be affected by sports teams’ group environment. Previous studies have analyzed the background and consequences of profiles of mood states, aiming at to understand which variables can affect or be affected thereby. However, the possible associative relationship of profiles of mood states and group cohesion, a variable pertaining to group environment, still demands new investigations. In this sense, in order to analyze possible associations between group cohesion and pre-competitive profile of mood states in youth athletes, a quantitative study with a cross-sectional cut was carried out. The sample was composed of 81 athletes, 62 boys (76.5%) and 19 girls (23.5%), aging from 14 to 17 y.o. (15.6±1.2), Basketball players (n=10; 12.3%), Indoor soccer (n=22; 27.1%), Soccer (n=16; 19.8%), and Volleyball (n=33; 40,8%), in pre-competitive phase. Data was collected at the training sites, one week prior to a State level competition. The Profile of Mood States (POMS) assessed the athletes’ pre-competitive mood states. This questionnaire has 42 items, assessed by a 5-point likert scale (1-5). The Group Environment Questionnaire – GEQ was used to evaluate group cohesion, composed of 16 items, assessed by a 9-point likert scale (1-9). Two questionnaires were gathered in one single electronic form. The Athletes were instructed on how to fill in the document, then, they were given tablets to fill in the electronic form individually. The average time was 11 minutes. For data analysis, the sample was dichotomized, pursuant to profile of mood states, into groups with iceberg profile and no iceberg profile. Data normality was verified by a Kolmogorov-Smirnov test. The correlations between dimensions of group cohesion and mood states were analyzed by the Spearman correlation coefficient. For the analysis of the predictive ability of group cohesion on profiles of mood states, a binary logistic regression model was used. The results indicate correlations of positive and significant dimension of group cohesion (p<0.05) with negative and significant dimension of mood force (p<0.05) with dimensions of stress, depression, anger, fatigue and confusion. All dimensions of group cohesion were significant predictors of profiles of mood states. The highest predictive statistical indicators were presented by dimensions of group integration – task (OR=2.372; IC=1.509-3.729; p<0,001) and cohesion task (OR=2.481; IC=1.477-4.167; p<0.001). From the results obtained, the hypothesis that higher levels of group cohesion are associated with better pre-competitive profiles of mood states in youth athletes can be confirmed. Thus, suggesting that the higher levels of group cohesion can positively impact the pre-competitive mood states of young athletes.